Penggunaan bahan bakar terbarukan (biodiesel-hydrogen) pada mesin Diesel Dual Fuel untuk mendukung Energy Transition di Indonesia - Kuntang Winangun; Atok Setiyawan; Bambang Sudarmanta; Ghulam Asrofi Buntoro; Robi Etdji Pangestu; Anas Nurgito; Tinovia Prasetyo (TURBO [Tulisan Riset Berbasis Online], 2023)
Increasing demand for oil as a fuel and declining production in refineries led to a nationwide fuel oil shortage. Hence compelling academics to develop answers, renewable energy is one of the proposed options. Compression ignition machines utilize renewable fuels such as biodiesel, crude palm oil (CPO), and hydrogen gas. Using biodiesel without modifying the engine can result in decreased thermal efficiency and increased smoke emissions. The addition of modest volumes of hydrogen gas can enhance the performance of diesel engines. The purpose of this investigation is to investigate the performance and emissions of diesel dual-fuel engines. In this investigation, a one-cylinder diesel engine with direct injection was operated at a constant 2000rpm with a 50 percent load. Flow variations of 2.5, 5, 7.5, and 10 liters per minute of hydrogen. Compared to biodiesel fuel, the results of this study indicate that a 10LPM hydrogen flow can boost thermal efficiency by 29.85% and a 7.5LPM hydrogen flow can increase power by 0.78 %. Moreover, the use of hydrogen gas reduces exhaust pollutants. Reduced HC, CO, and CO2 emissions by 26ppm, 0.01%, and 2.60%, respectively, for a 10LPM hydrogen flow.